2002
DOI: 10.1046/j.1365-2486.2003.00507.x
|View full text |Cite
|
Sign up to set email alerts
|

Northern hemisphere photosynthetic trends 1982–99

Abstract: We examined trends in the averaged May–September AVHRR normalized difference vegetation index (NDVI) from 1982 to 1999 for the northern hemisphere. NDVI is closely related to the amount of absorbed photosynthetically active radiation; hence, trends in NDVI reflect trends in photosynthetic activity of land‐surface vegetation. Linear and nonlinear trend analysis techniques were applied to four differently processed and corrected Advanced Very High Resolution Radiometer (AVHRR) NDVI data sets. The results were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
273
0
8

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 395 publications
(306 citation statements)
references
References 27 publications
25
273
0
8
Order By: Relevance
“…Most areas show an increase in NDVI for this period; the exceptions are the Sahara which shows no change and areas in the western parts of North America, south of the Amazon (South America), in central Asia, and central Australia, which show a decrease. Positive trends in similar NDVI data were reported in other studies as well [Myneni et al, 1997;Tucker et al, 2001;Slayback et al, 2003;Nemani et al, 2003]; the large negative excursion in NDVI during the early part of the time series, 1985-1986, makes a very important contribution to these trends. Compared to the control, both positive and negative trends in the fused AVHRR MODIS NDVI + CO 2 data (supporting information) are larger; the largest increases are found in western and central Europe and the highlands in eastern Africa.…”
Section: Trends In Annual Datasupporting
confidence: 87%
“…Most areas show an increase in NDVI for this period; the exceptions are the Sahara which shows no change and areas in the western parts of North America, south of the Amazon (South America), in central Asia, and central Australia, which show a decrease. Positive trends in similar NDVI data were reported in other studies as well [Myneni et al, 1997;Tucker et al, 2001;Slayback et al, 2003;Nemani et al, 2003]; the large negative excursion in NDVI during the early part of the time series, 1985-1986, makes a very important contribution to these trends. Compared to the control, both positive and negative trends in the fused AVHRR MODIS NDVI + CO 2 data (supporting information) are larger; the largest increases are found in western and central Europe and the highlands in eastern Africa.…”
Section: Trends In Annual Datasupporting
confidence: 87%
“…Even when NEP is enhanced, changes in disturbance regimes will affect NBP. Myneni et al (2001) observed C losses over much of Canada's boreal forests during the 1980s and 1990s despite the fact that increased photosynthetic activity had been observed during this same time period (Myneni et al 1997;Slayback et al 2003). These losses were brought about by increased disturbances (Kurz & Apps 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Chief among these are: (i) elevated atmospheric CO 2 concentrations, (ii) increased atmospheric N deposition, and (iii) longer growing seasons. The combined effect of these processes on the longerterm net C balance remains a topic of scientific discussion (Angert et al 2005;de Vries et al 2006;Euskirchen et al 2006), but remote sensing data suggest that these factors could be driving substantial increases in photosynthetic activity (Myneni et al 1997;Slayback et al 2003). Estimates suggest that net primary production (NPP) has increased by 6% globally during the 1980s and 1990s (Nemani et al 2003), and atmospheric inversion studies suggest that C storage in the boreal forest has been increasing since the early 1980s (Dargaville et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The GIMMS NDVI products, with a spatial resolution of 8 km, were compiled by merging segments (data strips) of a half-month period using the MVC method (Holben, 1986). These data had been calibrated for sensor shifts, and corrected to remove the effects of sensor degradation, satellite orbit drift, solar zenith angles and other factors, such as the effects of stratospheric aerosol loadings from the El Chichon and Mount Pinatubo eruptions in April 1984 and June 1991 (Zhou et al, 2001;Slayback et al, 2003).…”
Section: Ndvi Dataset From Gimmsmentioning
confidence: 99%